Challenges and Motivations of Science Communication: An Administrative Perspective at Land-Grant Universities - Ashley McLeod-Morin; Joy N Rumble; Ricky W Telg (Journal of Applied Communications, 2021)
Interdisciplinary agricultural research centers are becoming more common at land-grant universities. These centers often use an interdisciplinary approach to address complex science issues. As these centers address agricultural issues that impact society, effective science communication is a necessary activity. However, these centers may face unique barriers or opportunities. This study utilized a qualitative approach to identify the barriers and motivations of interdisciplinary agricultural center directors when communicating about science. Participants identified common science communication challenges, such as time and lack of funding. Funding was also identified as a motivation, as well as factors related to the tenure and promotion process. Recommendations from this work include evaluating the public relations and the effectiveness of science communication from these centers. Future research should also examine the financial structure of interdisciplinary centers to better inform best practices.
Keywords: science communication; qualitative; interdisciplinary science; Excellence Theory; public relations